Protective Effect of Selected Antioxidants on Naproxen Photodegradation in Aqueous Media - Kohei Kawabata; Ayaka Takato; Sayaka Oshima; Shiori Akimoto; Masanori Inagaki; Hiroyuki Nishi (MDPI AG, 2019)
A photostabilization strategy is an important aspect of quality assurance for photosensitive compounds. This study focused on the photoprotective effects of selected antioxidants including the effect of L-ascorbic acid (AA) on naproxen (NX) photodegradation in aqueous media. NX degradation during ultraviolet light (UV) irradiation and the protective effects of selected antioxidants were monitored by high-performance liquid chromatography (HPLC). The addition of AA induced the suppression of NX photodegradation, although the protective effect disappeared after AA was degraded completely. The results of the evaluations on the photoprotective effects on NX photodegradation and antioxidative activities of AA and other antioxidants showed that the protective effects of antioxidants are dependent on reducing power and photostability under UV irradiation. In this experiment, quercetin (QU) is the most effective antioxidant on account of the residual rate of QU after UV irradiation and the antioxidative activity in the potential antioxidant (PAO) test was significantly higher compared to other antioxidants following the higher protective effect on NX photodegradation.